The Effect of Project-Based Learning (PjBL) Based Audio Visual Media to Improve the Learning Outcomes of Grade VI Students of SD N 056613 Gemi Beach - Seni Sehati Br. Surbakti (Pusdikra-Publishing.com, 2024)
The research using the Influence of Audio Visual Media based on Project Based Learning (PjBl) is to improve students' critical thinking skills on the ecosystem subtheme on the learning outcomes of the science material